2006
DOI: 10.1074/jbc.m604858200
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Mucin Muc4 Induces Density-dependent Changes in ERK Activation in Mammary Epithelial and Tumor Cells

Abstract: The membrane mucin Muc4 has been shown to alter cellular behavior through both anti-adhesive effects on cell-cell and cellextracellular matrix interactions and its ability to act as an intramembrane ligand for the receptor tyrosine kinase ErbB2. The ERK pathway is regulated by both cell-matrix and cell-cell adhesion. An analysis of the effects of Muc4 expression on ERK phosphorylation in mammary tumor and epithelial cells, which exhibit both adhesion-dependent growth and contact inhibition of growth, showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…In contrast, in the presence of neuregulin, activation of both ErbB3 (neuregulin receptor) and ErbB2 was observed, which was further potentiated by rMuc4 and led to the downregulation of the p27 kip and an enhanced activation of ERK and Akt pathways. These changes in signaling pathways facilitated the cell cycle progression (96,99). Another important finding was made in polarized epithelial cells where exogenous expression of rMuc4 resulted in the localization of ErbB2 from the basolateral to the apical surface (87,97,100).…”
Section: Role Of Muc4 In Cancer Cell Signalingmentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast, in the presence of neuregulin, activation of both ErbB3 (neuregulin receptor) and ErbB2 was observed, which was further potentiated by rMuc4 and led to the downregulation of the p27 kip and an enhanced activation of ERK and Akt pathways. These changes in signaling pathways facilitated the cell cycle progression (96,99). Another important finding was made in polarized epithelial cells where exogenous expression of rMuc4 resulted in the localization of ErbB2 from the basolateral to the apical surface (87,97,100).…”
Section: Role Of Muc4 In Cancer Cell Signalingmentioning
confidence: 96%
“…In a recent study (99), Muc4 was shown to abrogate the contact inhibition of breast cancer cells and this effect was correlated with the size of the tandem-repeat domain. rMuc4 directed the distribution of E-cadherin from the lateral surface of the cells to the apical cell surface and an activation of ERK leading to an enhanced expression of cyclinD1 (99). This study added another dimension to the antiadhesive effect of MUC4 that allows indirect changes in cell signaling.…”
Section: Role In the Reversal Of Contact Inhibitionmentioning
confidence: 97%
“…Therapeutic blockade of ErbB2 with the monoclonal antibody trastuzumab improves the effectiveness of chemotherapy and survival in breast cancer (Vogel et al, 2002). In human mammary epithelial cells, MUC4 has an antiadhesive effect and appears to promote tumour growth and progression (Pino et al, 2006;Singh et al, 2007). In human pancreatic intraepithelial neoplasia, MUC4 expression increases progressively with advanced dysplasia (Swartz et al, 2002), and inhibition of MUC4 by antisense RNA suppresses cell growth and metastases in pancreatic cancer cells (Singh et al, 2004;Moniaux et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence shows that the ERK signaling pathway and RTEC dysfunction and attrition are central to the pathogenesis of kidney diseases [9,27]. MUC4 is reported as an activator of ERK signaling pathway in epithelial cells [28]. In the present study, it was found that silencing of MUC4 can inactivate the ERK signaling pathway and further restrain oxidative stress and CaOx crystal formation in RTEC, indicating that MUC4 may represent a potential investigative focus target in nephrolithiasis.…”
Section: Discussionmentioning
confidence: 51%
“…MUC4 can regulate cellular behavior through both antiadhesion functions on cell-extracellular matrix and cell-cell interactions and serving as an intramembranous ligand for the receptor tyrosine kinase ErbB2 [28]. The canonical ErkMAP kinase pathway has been demonstrated to be involved most frequently in the regulation of MUC4 expression [44].…”
Section: Discussionmentioning
confidence: 99%